Colorectal cancer deaths attributable to nonuse of screening in the United States - Meester, R.; Doubeni, C.; Lansdorp_Vogelaar, Iris; Goede, S.; Levin, T.; Quinn, V.; van Ballegooijen, M.; Corley, D.; Zauber, A. (Elsevier, 2015)
Purpose: Screening is a major contributor to colorectal cancer (CRC) mortality reductions in the United States but is underused. We estimated the fraction of CRC deaths attributable to nonuse of screening to demonstrate the potential benefits from targeted interventions. Methods: The established microsimulation screening analysis colon model was used to estimate the population attributable fraction (PAF) in people aged =50years. The model incorporates long-term patterns and effects of screening by age and type of screening test. PAF for 2010 was estimated using currently available data on screening uptake. PAF was also projected assuming constant future screening rates to incorporate lagged effects from past increases in screening uptake. We also computed PAF using Levin's formula to gauge how this simpler approach differs from the model-based approach. Results: There were an estimated 51,500 CRC deaths in 2010, about 63% (N ~ 32,200) of which were attributable to nonscreening. The PAF decreases slightly to 58% in 2020. Levin's approach yielded a considerably more conservative PAF of 46% (N ~ 23,600) for2010. Conclusions: Most of the current United States CRC deaths are attributable to nonscreening. This underscores the potential benefits of increasing screening uptake in the population. Traditional methods of estimating PAF underestimated screening effects compared with model-based approaches.